UN MODELO PSICOLÓGICO DE LA INTENCIONALIDAD - Gallardo, Alberto Miranda; Castro, Hilda Soledad Torres (European Scientific Journal, ESJ, 2015)
The purpose of this research is to present a theoretical model of intentionality; issue that has historically been poorly treated recently by philosophy and psychology. However, it is important to know that, from the emergence of cognitions, intentionality is a recurring theme. The model consists of an agent or perpetrator who acts intentionally and aims to achieve a goal. There are two ways of understanding the intent: first, as a conscious action from the outset planned, as when a trip to another country is carried out. The second, while mechanical, automatic, unconscious, as when driving a car expert, but the action can recognize consciously action at any time. In both situations the agent has the potential to feed back their behavior, whether or not reach the goal, which would self-regulate behavior and try again to achieve the intended purpose.